2004
DOI: 10.1261/rna.7350304
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing of a miRNA precursor: FIGURE 1.

Abstract: Micro RNAs comprise a large family of small, functional RNAs with important roles in the regulation of protein coding genes in animals and plants. Here we show that human and mouse miRNA22 precursor molecules are subject to posttranscriptional modification by A-to-I RNA editing in vivo. The observed editing events are predicted to have significant implications for the biogenesis and function of miRNA22 and might point toward a more general role for RNA editing in the regulation of miRNA gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
225
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(235 citation statements)
references
References 24 publications
7
225
1
2
Order By: Relevance
“…Recent studies showed that certain miRNA precursors are indeed edited by ADAR [18][19][20][21] . A systematic survey of human pri-miRNA sequences identified A→I RNA editing sites in ∼6% of all pri-miRNAs examined 21 .…”
Section: Editing Of Mirna Precursor Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that certain miRNA precursors are indeed edited by ADAR [18][19][20][21] . A systematic survey of human pri-miRNA sequences identified A→I RNA editing sites in ∼6% of all pri-miRNAs examined 21 .…”
Section: Editing Of Mirna Precursor Sequencesmentioning
confidence: 99%
“…Recent studies showed that precursor RNAs of certain miRNAs indeed undergo A→I RNA editing [18][19][20][21] , and editing seems to regulate the processing and expression of mature miRNAs 19 . Furthermore, one of the mammalian ADAR-family members sequesters siRNAs, thereby reducing RNAi efficacy 22 .…”
mentioning
confidence: 99%
“…Several studies have identified such editing within or near mature miRNA sequences (Luciano et al, 2004;Pfeffer et al, 2005;Blow et al, 2006). A-to-I editing potentially affects miRNA biogenesis as well as miRNA function.…”
Section: Mirnas: the Modificationsmentioning
confidence: 99%
“…The human miR-22 gene overlaps the exon 2 region of the spliced non-coding C17orf91 transcript, and primary miR-22 is processed from a capped, polyadenylated transcript (Cai et al, 2004;Rodriguez et al, 2004) (Supplementary Figure 1b). In addition, the miRNA editing event by adenosine-deaminases acting on RNA, was first described for the precursor miR-22 (Luciano et al, 2004) (Supplementary Figure 1c).…”
Section: Introductionmentioning
confidence: 96%